Investigation of natural infection of BALB C mice by Bartonella henselae - Luciene Silva dos Santos; Sayros Akyro Soares Martins; Francine Ramos Scheffer; Alexandre Seiji Maekawa; Rafaela de Paula Silva; Gabriel Rabelo de Araújo; Paulo Eduardo Neves Ferreira Velho; Marina Rovani Drummond (Brazilian Journal of Infectious Diseases)
Specific Pathogen-Free (SPF) animals are bred and maintained to exclude pathogens associated with significant morbidity or mortality, which may pose a risk to research replicability. The BALB/c strain is distributed globally and is among the most commonly used inbred strains in immunology and infectious disease research. Despite being a widely distributed bacterium that causes chronic infection, Bartonella henselae infection has not been investigated in any protocol that characterizes SPF animals. The objective of this study was to investigate the potential natural infection of laboratory animals of the BALB/c lineage by B. henselae. To achieve this, ten immunocompetent BALB/c mice were obtained directly from the bioterium and euthanized for collection of samples, including blood, skin, spleen, liver, heart, eye, kidney, intestine, esophagus, and brain. DNA was extracted using a commercial kit and tested via nested PCR for the ftsZ gene, as well as conventional PCR and qualitative real-time PCR using Sybr® Green for the citrate synthase gene (gltA), all specific reactions for B. henselae. All animals showed detection of B. henselae DNA in at least two different reactions in different tissues. The sequenced amplicons showed 100 % similarity to B. henselae. The use of mice infected by B. henselae in experiments is undesirable, as the bacteria can affect several aspects of the animal's physiology and consequently influence the results of the project, especially when subjected to immunosuppression. More studies are needed to understand and confirm the natural infection in experimental animals by Bartonella spp.. To date, no additional published reports of contamination of experimental animals by these bacteria have been identified.